Bimbingan Teknis Diversifikasi Olahan Udang di Smart Fisheries Village (SFV) Pengambengan Kabupaten Jembrana Bali - Perceka, Medal Lintas; Khairunnisa, Anis; Budiadnyani, I Gusti Ayu; Utari, Siluh Putu Sri Dia; Astiana, Ika; Farida, Iftachul; Samanta, Pinky Natalia; Cesrany, Mahaldika; Dewi, Resti Nurmala; Panjaitan, Fenny Crista A; Nugraha, I Made Aditya (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aimed to increase knowledge and understanding of the Processing and Marketing Group regarding the diversification of processed shrimp, packaging, and online product marketing. The method of implementing this service used technical guidance with 10 participants from Wijaya Fish Processing and Marketing Group. The evaluation instruments used were pre-test and post-test questions. Pre-test and post-test values were analysed using a t-test at 95% confidence intervals (Î± = 0,05). The results showed that there was an increase in knowledge and understanding of Wijaya Fish Processing and Marketing Group (P<0.05) regarding the diversification of vannamei shrimp processing, packaging, and online product marketing.